Pengaruh Inventory Intensity, Kinerja Keuangan, dan Tingkat Utang terhadap Tax Avoidance - Septiyana Hesti Kurnianingsih; Jasmi Indra (CV. ITTC INDONESIA, 2025)
This study aims to examine the effect of inventory intensity, financial performance, and debt level on tax avoidance in healthcare sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. A quantitative method with an associative approach was applied. The sample was selected using purposive sampling from a population of 37 companies, resulting in 10 companies, with 2 excluded as outliers. Data were analyzed using panel data regression with the assistance of EViews software. The best model was selected using the Chow and Hausman tests. The findings indicate that inventory intensity does not have a significant effect on tax avoidance, while financial performance has a significant negative effect and debt level has a significant positive effect. Simultaneously, the three independent variables significantly affect tax avoidance.